Nilai-Nilai Islam Dalam Pengelolaan Organisasi Pendidikan: Studi Atas Prinsip Syuro, Amanah dan Keadilan - Nadia Adiningrat; Nur Uswatun Hasanah; Abdul Fattah Nasution; Syahril Amin (Cemara Education and Science, 2026)
This study aims to examine the integration of Islamic values ​​in the management of educational organizations, emphasizing the principles of syuro, amanah, and justice. This study uses a qualitative approach through literature review, analyzing classical Islamic sources, books, and relevant scientific journals. The results of the study indicate that the principle of syuro serves as the basis for participatory decision-making, amanah serves as the foundation for leadership integrity and responsibility, and justice acts as a balancing force in creating organizational harmony and stability. The integration of these three principles forms an Islamic educational management system that is not only administratively effective but also grounded in ethical and spiritual values. Therefore, Islamic educational institutions need to consistently implement these values ​​to improve the quality of governance and achieve educational goals holistically.